Wear characteristics of Fe-C-Si and Fe-C-Al cast irons - Shaha, Sugrib Kumar; Haque, Md. Mohafizul; Khan, Ahsan Ali (Trans Tech Publications, Switzerland, 2011)
In order to study the wear properties of Fe-C-Si and Fe-C-Al alloy systems, castings were produced in resin bonded sand mould of suitable design, which provides information regarding various thicknesses of the castings. Gray cast iron is an inexpensive and readily available material used for manufacturing of roller, roller shell, piston rings, cylinder liners, etc. Its low melting point is characterized as unique combination of superior properties like good friction and wear properties and economic in manufacturing. In the present study, wear behavior of the Fe-C-Si and Fe-C-Al cast irons were investigated using a pin-on-disk type apparatus at room temperature. Alumina ball of 3 mm diameter was used as pin, while the cast sample served as the disk. The tests were carried out at a normal load of 5.0 N and a sliding velocity of 250 mm/s for 30 min. The Fe-C-Al cast iron showed a wear rate of 3.3203×10-5 mm3/m/N compared to 12.42×10-5 mm3/m/N of Fe-C-Si cast iron. The worn surfaces were analyzed using optical profilometer and SEM.